Outcastes in an "Egalitarian" society: Tamang/Blacksmith relations from Tamang perspective - Holmberg, David (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v10i0.1149 Occasional Papers in Sociology and Anthropology Vol.10 2007 p.124-140